2019
DOI: 10.1002/polb.24889
|View full text |Cite
|
Sign up to set email alerts
|

Challenge and Solution of Characterizing Glass Transition Temperature for Conjugated Polymers by Differential Scanning Calorimetry

Abstract: Thermomechanical properties of polymers highly depend on their glass transition temperature (T g). Differential scanning calorimetry (DSC) is commonly used to measure T g of polymers. However, many conjugated polymers (CPs), especially donor–acceptor CPs (D–A CPs), do not show a clear glass transition when measured by conventional DSC using simple heat and cool scan. In this work, we discuss the origin of the difficulty for measuring T g in such type of polymers. The changes in specific heat capacity (Δc p) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 83 publications
(120 reference statements)
0
36
0
Order By: Relevance
“…The T g of conjugated polymers is notoriously difficult to identify, because many such materials are semicrystalline and have rigid backbones. Signatures of T g in differential scanning calorimetry (DSC) scans are thereby suppressed 33 , although some unambiguous values have been summarized by Müller 34 . Alternatively, rheological measurements are sensitive to changes in mechanical properties, and can unambiguously locate the T g of conjugated polymers as the peak in the loss modulus as a function of temperature 8 .…”
mentioning
confidence: 99%
“…The T g of conjugated polymers is notoriously difficult to identify, because many such materials are semicrystalline and have rigid backbones. Signatures of T g in differential scanning calorimetry (DSC) scans are thereby suppressed 33 , although some unambiguous values have been summarized by Müller 34 . Alternatively, rheological measurements are sensitive to changes in mechanical properties, and can unambiguously locate the T g of conjugated polymers as the peak in the loss modulus as a function of temperature 8 .…”
mentioning
confidence: 99%
“…34 In addition, for the fully conjugated counterpart PNDI-C0, it shows a much higher chain rigidity with l k of 196 Å, we previously observed that it shows an extremely fast crystallization (e.g., less than 1 s) which cannot be suppressed even using a fast scanning chip calorimetry at a cooling rate up to 10,000 K/s. 59 Such a rapid crystallization process is presumably due to the rigid and planar backbone and strong π-π interaction. Due to the high-chain rigidity, chain folding in the ordered structure becomes difficult and hampered, hence, it is likely that the chains adopt a fringed micelle conformation, an extended crystalline morphology, in the ordered microstructure in solid state.…”
Section: Resultsmentioning
confidence: 99%
“…The material's property of P3HT, P3(4MP)T, and P3(3MP)T were reported in our previous work [49]. b Molecular weight information and regularity have been published in previous works [49,50]. second heating scans, and the values of T g and T m along with molecular weight information are tabulated in Table 1.…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…Before proceeding to the isothermal crystallization measurements, cooling experiments (10-100°C/min) were carried out on the conventional DSC and suggested that the crystallization of P3ATs cannot be suppressed with a cooling rate up to 100°C/min, as shown in Supplementary Fig. S2 [50]. Hence, FSC technique was utilized.…”
Section: Conventional Differential Scanning Calorimetrymentioning
confidence: 99%